1998
DOI: 10.1071/r97080
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation and fertilization, and subsequent development of buffalo (Bubalus bubalis) embryos: effects of oocyte quality and type of serum

Abstract: In Experiment 1, to determine the developmental potential of buffalo oocytes of different qualities, compact cumulus-oocyte complexes (COCs) with an unexpanded cumulus mass, and with homogeneous ooplasm were classified as Grade 1 (with > or =5 layers of cumulus cells) and Grade 2 less than 4 layers of cumulus cells). Grade-3 oocytes were either without cumulus cells or with expanded cumulus mass, and with irregular ooplasm. The oocytes were matured for 24 h at 38.5 degrees C, 5% CO2 in air in maturation medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 0 publications
2
67
1
1
Order By: Relevance
“…This system is complex and associated blastocyst yield is very low. Sub-optimal laboratory culture conditions for media preparation have been documented by Chauhan et al (1998) for buffalo in vitro fertilized embryos. These authors reported that the quality of water and chemicals used in media preparation may adversely affect in vitro embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…This system is complex and associated blastocyst yield is very low. Sub-optimal laboratory culture conditions for media preparation have been documented by Chauhan et al (1998) for buffalo in vitro fertilized embryos. These authors reported that the quality of water and chemicals used in media preparation may adversely affect in vitro embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the spermatozoa were processed by the method provided by Chauhan et al [13] and were taken from the same donor tested for IVF earlier. Briefly, two straws of frozen-thawed buffalo semen were washed twice with BO medium and the pellet obtained was resuspended in 0.5 ml of the capacitation-fertilization medium (BO).…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
“…The results for IVF in buffalo are very poor as compared to cattle because majority of IVF studies in buffalo use the protocols which are established for cattle (Yousaf and Chohan, 2003). The overall success rate of embryo production following IVF in buffalo is reported to be not more than 10-15 percent which is very low when compared to that of cattle (Chauhan et al, 1998;Nandi et al, 2001;Raghu et al, 2002). Nandi et al (2002) have reported approximately 80 percent of buffalo oocytes fail to reach the blastocyst stage and most of blastocysts are not capable of further development.…”
Section: Introductionmentioning
confidence: 87%